URBAN JOURNALISM AND THE NEW INTERNET TECHNOLOGIES - Estremadoyro, Julio (2008)
To understad tomorrow's journalism, a grasp of today's technologies is a must aseverything evolves rapidly especially participative journalism. To be better informed,Internet is the key to get a variety of news one is able to use amply. To use the Web isa right start.